Identifying And Ranking The Significant Causes Of Construction Delay In Private Hydropower Projects In Nepal - Koirala, Rajendra Prasad (Journal of Engineering Issues and Solutions, 2025)
Construction delays in hydropower projects causes a significant challenge to project completion and operations, particularly in Nepal’s private sector. This research aims to identify and rank the primary causes of delays using empirical data collected from stakeholders such as project engineers, managers, and developers. A qualitative research approach, including structured surveys, was employed to gather data from 34 private hydropower projects. Statistical analysis, including ranking techniques, was applied to identify the delay factors such as financial constraints, environmental issues, regulatory hurdles, and labor/material shortages. The findings also highlight that inefficiencies in project funding shortages, approval processes, and adverse weather conditions significantly impact project timelines. This study provides perilous perceptions for officials, investors, engineers and managers, suggesting efficient regulatory framework, boosted financial structuring, and improved stakeholder collaboration to mitigate delays. The recommendations aim to enhance project efficiency and contribute to the sustainable growth of Nepal’s hydropower industry.